Estudo da interação entre nanopartículas de ouro funcionalizadas e moléculas doadoras e aceitadoras de elétrons: um estudo por primeiros princípios - Ananias Borges Alencar (2012)
Gold nanoparticles have received considerable attention because of their promising applications. In this work, we studied the interaction between gold nanoparticles with thiolate protecting ligands and donor molecules (tetrabutylammonuim) or acceptor molecules (hexafluorophosphate). The investigation of the system properties was performed by first-principles calculations based on the Density Functional Theory. Two models of nanoparticles were used, each one having three different sizes, by varying of the size of thiolate ligand. We investigatedthe relative stability between the systems, the relative distances between the centers of mass of the nanoparticle and the dopant, and the effect of doping. Our results show that the equilibrium distances between the acceptor dopants, and the center of mass of the nanoparticle are smallerthose for the donor dopant. It was also observed that the charge transfer behavior is approximately linear with the number of dopants to the acceptor dopant, up to a critical number of dopants.